ELSAMI (ELECTRONIC SADAQAH FOR MICROBUSINESS) - Pradana, Eferanda Risqyta (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstrack: World Bank data states that there are 48% of households that have saved or deal with banks. This means that the remaining 52% is not affordable, so businesses cannot develop. The solution in the form of a Sharia Business Loan (PUSYAR) has been carried out by the Mojokerto Government to overcome this problem. PUSYAR is an Islamic financial instrument that provides financing to micro businesses. PUSYAR still has some disadvantages in providing assistance to micro businesses or in supporting financial inclusion. The main problem from the community side is the inconsistency of the number of sadaqah, and the community does not get assistance in the PUSYAR program so that the business undertaken is not sustainable or confused with the existing contract. We have innovated by making a grand-design application for ELSAMI (Electronic Sadaqah for Microbusiness) as a financial inclusion that can increase the sustainability of micro businesses. This application will contain information starting from the introduction of the program, the type of program, the number of micro businesses as a place for channeling funds and can make it easier for people to share their beliefs online. Keywords: Financial Inclusion, Microbussiness, Pusyar, ELSAMI, Sadaqah